Review on SGLT2 Inhibitors - Kale, Namrata; Dighe, Pravin (Asian Journal of Pharmaceutical Research and Development, 2023)
The pharmaceutical industry employs a variety of analytical techniques to test the quality, concentration, and composition of medicines in biological fluids. This review work to provide the most existing analytical methods for the analysis of SGLT2 inhibitors (Empagliflozin, Dapagliflozin, Canagliflozin) in active pharmaceutical ingredients, biological fluids & pharmaceutical dosage forms. SGLT2 inhibitors are gliflozin derivatives, used generally in the treatment of type 2 diabetes mellitus. These inhibitors have pharmacological action in the kidneys, where they filter and reabsorb glucose in the proximal convoluted tubule and help to contribute to glucose homeostasis. The analytical techniques such as HPLC, LC-MS/MS, Mass spectrometry, UV-spectroscopy, and HPTLC on selected SGLT2 inhibitors were reviewed.